Battery formation method, battery
By adding a first additive of a specific structure and a second additive of a dinitrile substance to the battery electrolyte, combined with the optimized current and termination voltage, the problem of insufficient battery capacity is solved, and the cycling performance and high temperature of the battery are significantly improved. performance.
Patent Information
- Application Number
- CN202411497964.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Existing batteries have many problems in capacity, which are difficult to meet the needs of small size, large capacity, light weight and high energy density.
Using a battery-making method, an electrolyte additive, including a first additive and a second additive, is added to the electrolyte solution. The first additive satisfies a specific structural formula, and the second additive is a dinitrile substance. By optimizing the processed current and termination voltage, a dense and complete sulfur-containing interface mask is formed to fully activate the positive electrode active material.
It improves the circulating performance and high-temperature performance of the battery, forms a high-quality interface mask, reduces the occurrence of side reactions, and extends the service life of the battery.
Smart Images

Figure CN119009211B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular, to a battery formation method and a battery. Background Art
[0002] With the rise of consumer electronic products such as smartphones, tablets, wearable devices and drones, the demand for 3C consumer battery materials has experienced an unprecedented explosion. Currently, 3C digital electronic products are developing in the direction of light, thin, short and small, and the demand for batteries with small size, large capacity, light weight and high energy density is showing a trend of further rapid growth. However, there are still many problems with the capacity of current batteries. Summary of the invention
[0003] In a first aspect of the present application, the present application proposes a battery formation method, wherein the electrolyte of the battery includes an electrolyte additive, and the electrolyte additive includes: a first additive, and the first additive satisfies at least one of the following structural formulas:
[0004] Formula 1-1, 1-2, Formula 1-3
[0005] Formula 1-4 Formula 1-5, the second additive, the second additive includes a dinitrile substance; the chemical formation method includes: a first chemical formation treatment, the current of the first chemical formation treatment is 0.05C-0.1C; a second chemical formation treatment, the current of the second chemical formation treatment is greater than the current of the first chemical formation treatment. Thus, it is helpful to form a dense and complete sulfur-containing interface film on the surface of the active material, and the positive electrode active material can be fully activated to improve the cycle performance and high temperature performance of the battery.
[0006] In some embodiments, the current of the second formation treatment is 0.3C-0.5C, thereby facilitating rapid activation of active materials and early identification of possible defects of the battery.
[0007] In some embodiments, the termination voltage of the first formation treatment is 3.3 V-3.8 V, and the termination voltage of the second formation treatment is 3.9 V-4.2 V. This helps to form an interface film with better film quality and fully activate the active material.
[0008] In some embodiments, the temperatures of the first chemical formation treatment and the second chemical formation treatment are independently 45° C. to 80° C. This helps to quickly and evenly form an interface film and activate the active material.
[0009] In some embodiments, the second formation treatment further includes: an aging treatment, wherein the temperature of the aging treatment is 40° C.-50° C., and the time of the aging treatment is 24 hours-36 hours, thereby facilitating the full discharge of gas inside the battery and removing internal polarization.
[0010] In some embodiments, the dinitrile substance includes at least one of succinonitrile, 1,2-bis(cyanoethoxy)ethane, ethylene glycol bis(propionitrile)ether, glutaronitrile, adiponitrile, trans-butenedinitrile, trans-hexenedinitrile, and 1,4-dicyano-2-butene. Thus, trace amounts of water, hydrogen fluoride and other impurities in the electrolyte can be effectively removed, and the film-forming effect can be improved.
[0011] In some embodiments, the mass fraction of the first additive in the electrolyte is w1, the mass fraction of the second additive in the electrolyte is w2, and w1 / w2 is 0.1-1. Thus, the first additive and the second additive can fully participate in the formation of the interface film.
[0012] In some embodiments, w1 is 0.1%-5%, and / or w2 is 0.5%-6%.
[0013] In some embodiments, a third additive is further included, and the third additive includes 1,3-propane sultone. Thus, the cycle performance of the battery can be further improved.
[0014] In some embodiments, the mass fraction w3 of the third additive in the electrolyte is 0.5%-3%.
[0015] In the second aspect of the present application, the present application proposes a battery obtained by the aforementioned formation method. Therefore, the battery has all the characteristics and advantages of the aforementioned formation method, which will not be described in detail here.
[0016] In some embodiments, a positive electrode sheet is included, the positive electrode sheet includes a positive current collector and a positive active material layer located at least on one side of the positive current collector, the positive active material layer includes a positive active material, and the positive active material includes a lithium cobalt oxide material. Thus, the battery has a higher energy density and a better cycle life. DETAILED DESCRIPTION
[0017] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0018] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0019] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.
[0020] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.
[0021] During the production and manufacturing process of the battery, the formation process helps the electrolyte additives to form a passivation interface film on the surface of the electrode. This interface film plays a key role in stabilizing the active materials and preventing the electrolyte from further decomposing. It also helps to gradually activate the positive electrode active materials and the negative electrode active materials, so that the lithium ions in the electrolyte react to form a stable electrochemical structure. In the present application, the formation process is optimized for the electrolyte additive combination, which significantly improves the film-forming quality of the electrolyte additive combination, thereby improving the battery performance. In view of this, in the present application, by optimizing the electrolyte additives compatible with the high-voltage positive electrode active materials and forming a high-quality SEI film by controlling the formation current, the cycle performance and high-temperature performance of the battery performance are significantly improved.
[0022] In a first aspect of the present application, the present application proposes a battery formation method, wherein the electrolyte of the battery includes an electrolyte additive, and the electrolyte additive includes: a first additive, and the first additive satisfies at least one of the following structural formulas:
[0023] Formula 1-1, 1-2, Formula 1-3
[0024] Formula 1-4 Formula 1-5, the second additive, the second additive includes a dinitrile substance; the chemical formation method includes: a first chemical formation treatment, the current of the first chemical formation treatment is 0.05C-0.1C; a second chemical formation treatment, the current of the second chemical formation treatment is greater than the current of the first chemical formation treatment. Thus, it is helpful to form a dense and complete sulfur-containing interface film on the surface of the active material, and the positive electrode active material can be fully activated to improve the cycle performance and high temperature performance of the battery.
[0025] During the formation process of the battery, the first additive can participate in the formation of the interface film at both the positive and negative electrodes, forming an inorganic component interface film rich in sulfur, effectively reducing interface side reactions. However, the vinyl sulfate group in the first additive is sensitive to trace moisture in the battery, and is easily reacted with water to form by-products, and the by-products are easily decomposed and gasified under high temperature conditions, causing the battery performance to deteriorate. By adding the second additive, the reaction between its cyanide group and water can be used to remove trace water in the battery and reduce the occurrence of side reactions of the first additive; it can also participate in the positive electrode film formation at the same time, further inhibiting the side reaction of electrolyte oxidation at the positive electrode interface, and alleviating the dissolution of transition metals in the positive electrode active material. The first additive and the second additive can be used together to improve the cycle performance and high temperature performance of the battery.
[0026] On this basis, when the current of the first formation treatment is 0.05C-0.1C, the small current charging time is long, which helps the additive to participate more fully in the formation of the interface film and ensure the compactness and stability of the interface film. The first additive participates in the formation of the interface film at both the positive and negative electrodes, promotes the participation of inorganic components in the construction of the interface film, and enhances the stability of the SEI film, thereby improving the battery's cycle performance and high temperature performance. After reaching the film-forming potential of the second additive in the second formation stage, it can be adsorbed on the positive electrode surface and participate in the construction of the positive electrode CEI film. The cyanide group in its structure forms a strong interaction with the metal ions on the positive electrode surface, further forming a stable, uniform, low-impedance interface film, which can improve the integrity of the high-voltage positive electrode active material and reduce the side reactions that occur when the positive electrode active material is in direct contact with the electrolyte under high voltage conditions. When the current of the second formation treatment is greater than that of the first formation treatment, the excessive consumption of electrolyte additives can be suppressed, and the amount of liquid loss during the formation process can be reduced, so that the density of the formed interface film is moderate, the internal resistance of the battery is small, and the consistency and stability of the interface film can be further improved by increasing the electrochemical reaction rate and the film formation rate. This helps to form a dense and complete sulfur-containing interface film on the surface of the active material, and can fully activate the positive electrode active material, thereby improving the cycle performance and high temperature performance of the battery.
[0027] As an example, the current of the first formation treatment may be 0.05C, 0.06C, 0.07C, 0.08C, 0.09C, or 0.1C.
[0028] When the current of the first formation treatment is within the aforementioned range, it helps to form a uniform and dense interface film, reduce the occurrence of side reactions inside the battery during the formation process, and uniformly embed lithium ions.
[0029] In some embodiments, the current of the second formation treatment is 0.3C-0.5C.
[0030] As an example, the current of the second formation process may be 0.3C, 0.35C, 0.4C, 0.45C, or 0.5C.
[0031] When the current of the second formation treatment is within the aforementioned range, it helps to quickly and fully activate the active material, allowing the battery to exert its maximum capacity as much as possible, and can accelerate battery aging, which helps to identify possible battery defects at an early stage.
[0032] In some embodiments, the termination voltage of the first formation treatment is 3.3 V-3.8 V, and the termination voltage of the second formation treatment is 3.9 V-4.2 V. This helps to form an interface film with better film quality and fully activate the active material.
[0033] When the formation treatment includes the first formation treatment and the second formation treatment carried out in sequence, the termination voltage of the second formation treatment is greater than the termination voltage of the first formation treatment. Under the current range of the aforementioned first formation treatment, when the termination voltage of the first formation treatment is within the aforementioned range, the time of the first formation treatment is moderate, which not only helps the sufficient film formation of the electrolyte additive, but also can reduce the increase of the internal impedance caused by the film formation being too dense. Under the current range of the aforementioned second formation treatment, when the termination voltage of the second formation treatment is within the aforementioned range, the time of the second formation treatment is moderate, and helps the battery to reach a stable state faster, improves the stability of electrical performance.
[0034] In some embodiments, the temperatures of the first chemical formation treatment and the second chemical formation treatment are independently 45° C. to 80° C. This helps to quickly and evenly form an interface film and activate the active material.
[0035] As an example, the temperature of the first formation treatment may be 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.
[0036] As an example, the temperature of the second formation treatment may be 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.
[0037] In some embodiments, the second formation treatment further includes: an aging treatment, wherein the temperature of the aging treatment is 40° C.-50° C., and the time of the aging treatment is 24 hours-36 hours, thereby facilitating the full discharge of gas inside the battery and removing internal polarization.
[0038] As an example, the temperature of the aging process may be 40°C, 42°C, 44°C, 46°C, 48°C, or 50°C.
[0039] As an example, the aging treatment time may be 24 h, 26 h, 28 h, 30 h, 32 h, 34 h or 36 h.
[0040] When the temperature and time of the aging treatment are within the aforementioned range, it is helpful to fully discharge the small molecule gas formed by the side reaction in the battery during the formation process, and will not cause excessive consumption of the electrolyte additives at high temperature.
[0041] In some embodiments, between the first formation treatment and the second formation treatment, the method further includes: subjecting the battery to a static treatment for 3 minutes to 10 minutes.
[0042] In some embodiments, both the first formation process and the second formation process may be constant current charging.
[0043] In some embodiments, the dinitrile substances include at least one of succinonitrile (SN), 1,2-bis(cyanoethoxy)ethane, ethylene glycol bis(propionitrile) ether (DENE), glutaronitrile, adiponitrile (ADN), trans-butenedinitrile, trans-hexenedinitrile, and 1,4-dicyano-2-butene. Thus, trace amounts of water, hydrogen fluoride and other impurities in the electrolyte can be effectively removed, and the film-forming effect can be improved.
[0044] In some embodiments, the mass fraction of the first additive in the electrolyte is w1, the mass fraction of the second additive in the electrolyte is w2, and w1 / w2 is 0.1-1.
[0045] As an example, w1 / w2 may be 0.1, 0.5, 0.7 or 1.0.
[0046] When w1 / w2 is within the aforementioned range, the synergistic effect between the first additive and the second additive is better, and they can fully participate in the formation of the interface film.
[0047] In some embodiments, w1 is 0.1%-5%, and / or w2 is 0.5%-6%.
[0048] As examples, w1 may be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%.
[0049] As an example, w2 may be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%.The second additive may effectively remove trace amounts of water in the battery.
[0050] In some embodiments, a third additive is further included, the third additive including 1,3-propane sultone.
[0051] The third additive can continuously repair the interface film during the cycle of the battery and improve the cycle performance of the battery.
[0052] In some embodiments, the mass fraction w3 of the third additive in the electrolyte is 0.5%-3%.
[0053] As examples, w3 may be 0.5%, 1%, 1.5%, 2%, 2.5%, or 3%.
[0054] It should be noted that since the first additive, the second additive and the third additive will participate in the formation of the interface film on the surface of the active material during the formation process and thus be partially consumed, the actual detected amount of the above substances in the battery will be slightly smaller than their added amount.
[0055] In the second aspect of the present application, the present application proposes a battery obtained by the aforementioned formation method. Therefore, the battery has all the characteristics and advantages of the aforementioned formation method, which will not be described in detail here.
[0056] In some embodiments, a positive electrode sheet is included, the positive electrode sheet includes a positive current collector and a positive active material layer located at least on one side of the positive current collector, the positive active material layer includes a positive active material, and the positive active material includes a lithium cobalt oxide material. Thus, the battery has a higher energy density and a better cycle life.
[0057] By increasing the battery's charge termination voltage, a higher capacity can be achieved. When the charge termination voltage increases, the electrolyte is prone to irreversible chemical reactions with the positive electrode active material, continuously consuming active lithium, and adverse side reactions such as transition metal dissolution and large amounts of gas generation will occur on the positive electrode side, ultimately leading to irreversible phase changes in the material and a serious reduction in the battery's cycle performance. In the present application, the aforementioned combination of electrolyte additives and an optimized formation method are helpful in forming a dense and stable interface film on the surface of the positive electrode active material, reducing the occurrence of side reactions between the positive electrode active material and the electrolyte, inhibiting the dissolution of transition metals in the positive electrode active material, and improving the battery's cycle performance.
[0058] In some embodiments, the electrolyte contains a non-aqueous organic solvent, and the non-aqueous organic solvent includes two or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, ethyl butyrate, methyl propyl carbonate, halogenated ethylene carbonate, propylene carbonate, methyl propyl carbonate, γ-butyrolactone, γ-valerolactone, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 2,2-difluoroethyl acetate.
[0059] As an example, the weight percentage of the non-aqueous organic solvent in the electrolyte is 50%-80%.
[0060] In some embodiments, the electrolyte solution contains an electrolyte lithium salt, and the electrolyte lithium salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, lithium bis(trifluoromethylsulfonyl)imide, and lithium difluoride sulfonylimide.
[0061] As an example, the weight percentage of the electrolyte lithium salt in the electrolyte solution is 10%-18%.
[0062] In some embodiments, a negative electrode plate is included. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed at least on one side of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of nano-silicon, silicon oxide material (SiO X , 0 < x < 2), silicon-carbon material, artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.
[0063] The solutions of the present application are described below through specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be regarded as limiting the scope of the present application. For those not specifying specific techniques or conditions in the examples, the techniques or conditions described in the literature in the art or according to the product specifications are followed. For the reagents or instruments not indicating the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0064] Example 1
[0065] 1) Preparation of the electrolyte solution: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed according to a mass ratio of EC:PC:DEC:PP = 2:1:3:3, and then lithium hexafluorophosphate (LiPF6) is added until the molar concentration is 1 mol / L. The first additive is the substance shown in Formula 1-1, and the mass fraction of the first additive in the electrolyte solution is 2 wt%. The second additive is adiponitrile, and the mass fraction of the second additive in the electrolyte solution is 4 wt%. The third additive is 1,3-propane sultone, and the mass fraction of the third additive in the electrolyte solution is 1 wt%.
[0066] 2) Preparation of the positive electrode plate: The positive electrode active material LiCoO2, conductive carbon black, and binder PVDF are dispersed in a non-aqueous organic solvent NMP (N-methylpyrrolidone) according to a weight ratio of 96:2:2 and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil positive electrode current collector, and after drying, rolling, and cutting, a positive electrode plate is obtained.
[0067] 3) Preparation of negative electrode sheets: Silicon-carbon material, conductive carbon black, binder styrene-butadiene rubber and carboxymethyl cellulose are dispersed in deionized water in a mass ratio of 96:1:1.2:1.8 to obtain negative electrode slurry, which is coated on both sides of copper foil, dried, rolled and vacuum dried, and welded with nickel lead wires using an ultrasonic welder to obtain negative electrode sheets.
[0068] 4) Preparation of lithium-ion batteries: Place a polyethylene microporous membrane with a thickness of 20 μm between the positive electrode and the negative electrode as a separator, then wind the sandwich structure consisting of the positive electrode, negative electrode and separator, flatten the winding body and put it into the aluminum-plastic film, lead out the lead wires of the positive and negative electrodes respectively, and then heat-press and seal the aluminum-plastic film to obtain the battery cell to be injected with liquid. Inject the prepared electrolyte into the dried battery cell, and complete the preparation of the lithium-ion battery after vacuum packaging, standing, formation, shaping, and capacity division.
[0069] 5) Formation process: First formation treatment: at 50°C, charge to 3.5V at 0.05C constant current. After the first formation treatment, let it stand for 3 minutes. Then, perform the second formation treatment: at 50°C, charge to 4.2V at 0.3C constant current. After the second formation treatment, age at 40°C for 24 hours.
[0070] The remaining embodiments and comparative examples are consistent with embodiment 1, and the differences are shown in Table 1 and Table 2.
[0071] Table 1
[0072]
[0073] Table 2
[0074]
[0075] The batteries in the above-mentioned embodiments and comparative examples were tested as follows. The test results are shown in Table 3.
[0076] 1) Cycling performance at room temperature: Place the battery in a 25°C environment, charge it at a constant current of 1C to a rated voltage of 4.5V, charge it at a constant voltage of 4.5V to a cut-off current of 0.05C, leave it for 5 minutes, then discharge it at a constant current of 1C to 3.0V, leave it for 5 minutes. This is a charge and discharge cycle. Repeat the charge and discharge for 500 cycles, and record the discharge capacity C of the 500th cycle. 500 The capacity retention rate is obtained by dividing it by the discharge capacity C0 of the first cycle.
[0077] 2) High temperature cycle performance: Place the battery in a 45°C explosion-proof oven, charge at 1C constant current to the rated voltage of 4.5V, charge at 4.5V constant voltage to a cut-off current of 0.05C, leave for 5 minutes, then discharge at 1C constant current to 3.0V, leave for 5 minutes. This is a charge and discharge cycle. Repeat the charge and discharge for 500 cycles, and record the discharge capacity C of the 500th cycle. 500 The capacity retention rate is obtained by dividing it by the discharge capacity C0 of the first cycle.
[0078] 3) High temperature storage performance: Charge at 1C constant current to rated voltage at 25°C, charge at constant voltage to cut-off current 0.05C, leave for 5 minutes, then discharge the battery at 1C constant current, the first discharge capacity is recorded as C0, the battery thickness is recorded as D0, and then place the battery in a 60°C explosion-proof oven. After storage for 14 days, the battery thickness D1 is tested in the oven, and then the battery is taken out and cooled to room temperature, and its discharge retention capacity C2 of 1C discharge to 3.0V is tested, and then the charge and discharge steps are repeated for 3 weeks. Record the battery's third week discharge capacity C3, thickness expansion rate = (D1-D0) / D0×100%, capacity retention rate = (C2 / C0)×100%, capacity recovery rate = (C3 / C0)×100%.
[0079] Table 3
[0080]
[0081] The cycle performance and high temperature performance of the battery in the embodiment are better than those of the battery in the comparative example. Specifically, Example 1-Example 3, Example 15-Example 16 show that when the current of the first formation treatment is moderate, the first additive is consumed more fully, and the quality of the SEI film formed is good, which can effectively improve the cycle performance and high temperature performance of the battery. Example 1, Example 4-Example 7 show that when the current of the second formation treatment is moderate, the consumption degree of the additive can be effectively controlled. On the one hand, the SEI film formed by the first additive has high integrity and low impedance, which is conducive to improving the cycle performance and high temperature performance; on the other hand, the first additive and the second additive both participate in the formation of a dense and uniform CEI film at the positive electrode, which is conducive to reducing the inhibition of electrolyte decomposition and reducing transition metal dissolution. When the current of the second formation treatment is large, the additive will not be fully consumed, and the interface film formed will be incomplete, thereby slightly deteriorating the cycle performance and high temperature performance; when the current of the second formation treatment is small, the additive will be over-consumed, and the interface film formed will be too dense, resulting in increased impedance, thereby slightly deteriorating the cycle performance and high temperature performance. Example 1, Example 8-Example 10, Comparative Example 4-Comparative Example 5 show that when the termination voltage of the first formation treatment is moderate, the SEI film formation potential can be reached and the film formation reaction is relatively complete, and the impedance is low. When the termination voltage of the first formation treatment is small, the film formation potential of the first additive cannot be reached, and the film can only be formed in the second stage, resulting in insufficient film formation time, incomplete film formation reaction, or reaching the film formation potential, but the film formation time in the first stage is still insufficient, the first additive is not completely consumed, and the film formation is not dense enough, thereby slightly degrading the cycle performance and high temperature performance; when the termination voltage of the first formation treatment is too large, the film formation time is too long, the first additive will be over-consumed, and the second additive will participate in the film formation during the first formation treatment, and the interface film formed at the positive and negative electrodes is eventually too dense, and the battery impedance increases, thereby slightly degrading the cycle performance and high temperature performance. Example 11-Example 13, Comparative Example 5 show that the termination voltage of the second formation treatment has a similar effect on the film quality as the termination voltage of the first formation treatment. Among them, the effect of the termination voltage of the first formation treatment on the film quality is greater than the effect of the termination voltage of the second formation treatment. Example 1 and Example 14 show that proper aging treatment is beneficial to remove internal polarization of the battery, increase battery capacity, and reduce impedance. Example 1 and Examples 17-24 show that when the ratio of the first additive to the second additive is appropriate, it helps to improve the storage performance and high temperature performance of the battery. Example 25-31, Comparative Example 6-Comparative Example 7 show that the appropriate combination of the first additive and the second additive can improve the storage performance and high temperature performance of the battery. Example 1 and Example 32 show that the third additive is beneficial to continuously repair the SEI film and inhibit the gas production of the battery cell, so that the cycle performance and high temperature performance are further improved.
[0082] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A battery formation method, characterized in that: The electrolyte of the battery includes an electrolyte additive, and the electrolyte additive includes: The first additive satisfies at least one of the following structural formulas: Formula 1-1, 1-2, Formula 1-3 Formula 1-4 Formula 1-5, a second additive, wherein the second additive comprises a dinitrile substance; The formation method comprises: A first formation treatment, wherein the current of the first formation treatment is 0.05C-0.1C, and the termination voltage of the first formation treatment is 3.3V-3.8V; The second formation treatment, the current of the second formation treatment is greater than the current of the first formation treatment, the current of the second formation treatment is 0.3C-0.5C, and the termination voltage of the second formation treatment is 3.9V-4.2V.
2. The method according to claim 1, characterized in that: The temperatures of the first chemical formation treatment and the second chemical formation treatment are independently 45° C. to 80° C.
3. The method according to claim 1, characterized in that The second chemical formation treatment further includes: an aging treatment, the temperature of the aging treatment is 40° C.-50° C., and the time of the aging treatment is 24 hours-36 hours.
4. The method according to claim 1, characterized in that: The dinitrile substances include at least one of succinonitrile, 1,2-bis(cyanoethoxy)ethane, ethylene glycol bis(propionitrile) ether, glutaronitrile, adiponitrile, trans-butenedinitrile, trans-hexenedinitrile, and 1,4-dicyano-2-butene.
5. The method according to claim 4, characterized in that The mass fraction of the first additive in the electrolyte is w1, the mass fraction of the second additive in the electrolyte is w2, and w1 / w2 is 0.1-1.
6. The method according to claim 5, characterized in that w1 is 0.1%-5%, and / or, w2 is 0.5%-6%.
7. The method according to claim 1, characterized in that Also included is a third additive comprising 1,3-propane sultone.
8. The method according to claim 7, characterized in that The mass fraction w3 of the third additive in the electrolyte is 0.5%-3%.
9. A battery, characterized in that: The product is obtained by the chemical formation method according to any one of claims 1 to 8.
10. The battery according to claim 9, characterized in that The invention comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer at least located on one side of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a lithium cobalt oxide material.
Citation Information
Patent Citations
Lithium ion battery
CN115020814A